PENGARUH PELATIHAN GOAL SETTING UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MAHASISWA - Setiawan, Nugroho Arief (Universitas Islam Negeri Raden Intan Lampung, 2019)
ABSTRACT The purpose of this research was to obtain the effect of goal setting training in improving students motivation to learn. The hypothesis of this study that there were a difference between the level of student learning motivation experiment group with control group were given before and after goal setting training. Students are given goal setting training (experiment group) will increase the learning motivation after treated by goal setting training than students who did not receive goal setting training (control group). Subjects in this study amounted to eighteen for the experimental group and also for the control group. Measuring instruments used to measure the level of learning motivation was learning motivation scale. Experimental design used in this study was Pre-Test Post-Test Control Group Design and the process of determining the subject done randomly. The analysis used was a parametric statistical test models of the Independent Sample T - Test to see differences in learning motivation scores between the experimental group with the control group. The results of the pretest data analysis using Independent Sample T-Test known sig = 0.798 ( p > 0.05), and posttest data analysis known sig = 0.000 ( p < 0.005 ). Meanwhile, to see the difference in pretest scores, posttest, and follow-up used paired sample T-test in the experimental group and the control group. The results of data analysis used Paired Sample T-Test on the pretest-posttest scores showed t = -23.884 with a significance level = 0.000 (p< 0.005), the results of the analysis on the posttest-follow-up scores showed t = 4,481 with a significance level = 0.000 (p< 0.005), and the results of the analysis on the pretest score-followup showed t = -20 821 with a significance level = 0.000 (p<0.005). The results of this analysis showed that the experimental group treated with increased motivation to learn after being given the training goal setting than before given the goal setting training. Keywords: goal setting training, learning motivation